Predictors of Treatment Outcomes in Endemic Burkitt's Lymphoma Patients at Jaramogi Oginga Odinga Teaching and Referral Hospital, Kisumu County - Onyango, Lamek (JOOUST, 2017)
Endemic Burkitt's lymphoma is the most common childhood cancer in equatorial Africa, where it is about ten times more common than in Europe. It also is the most prevalent pediatric malignancy among children in Western Kenya. Although it is highly responsive to chemotherapy, the number of its mortality cases associated with it is still high and the underlying reasons for .this high mortality rates is still unknown. Therefore, this study describes the demographical and clinical characteristics of eBL patients observed over time and determines the influence of these characteristics on eBL patient treatment outcome at Jaramogi Oginga Odinga Teaching and Referral Hospital (JOOTRH). This was a retrospective study design intended to describe the clinical and demographical characteristic and their influence on the treatment outcome of eBL patients. A total of 178 eBL children (103 boys and 75 girls, with a mean age of 7.37 years) who were diagnosed between 2009 and 2014 were enrolled in the study. There was no significant difference in the proportion of boys and girls, and the mean age (7.37 years) at diagnosis remained similar throughout the 'study period. Those presenting with abdominal tumor only were 72 (40.40%) while those with facial tumor only were 28 (15.70%). Children presenting with a combination of abdominal and facial tumor were 23 (12.90%). HIV positivity was 3.9 %, and did not differ between different periods. A total of 125 (70.2%) children received induction chemotherapy phase and they had no significant difference in proportion throughout the study period. fu addition 108 ( 60. 7%) of the children received consolidation phase of chemotherapy while only 35 (19.7%) received maintenance phase of chemotherapy. In terms of eBL patients response to chemotherapy, 49°(27.5%) did not respond, 59 (33.2%) had complete remission, 33 (18.5%) had partial remission, 31 (15.0%) had stable disease, while 18 (5.0%) had relapse. But there were no changes in the proportions in response to chemotherapy. Hematological indices revealed that 46 (26.1%) had severe anemia, 110 (62.5%) had mild anemia while only 20 (11.4%) had normal anemia levels. A total of 62 (34.83%) children died during the follow up; analysis also revealed that 13 of the children who received all phases of consolidation chemotherapy died while 6 died despite receiving maintenance chemotherapy. There was no significant difference in mortality rates in children with symptoms of fever (p=0.095), weight loss (p=0.403), night sweats (p=0.165), severe infection (p=0.774) and malaria (p=0.343). Children presenting with testicular tumour (HR 31.77, 95% C.I 3.28-307.62, p=0.003) and lung parenchymal tumour (HR 8.65, 95%C.I 2.00- 37.24, p=0.004) had increased mortality rate relative to those presenting with other tumors. There was no statistical difference in the children mortality rate by HIV status (HR 1.3 7, 95% C.I 0.60-3.13, p=0.455). Further analysis revealed that those with severe anemia had increased mortality rate (HR 2.07, 95% C.I 3.67-0.97, p=0.012). Endemic Burkitt's lymphoma is more prevalent among male children at the age of 5-9 years. Patients who completed the entire treatment cycle up to maintenance therapy had low mortality rate. However, patients who presented with lung parenchyma, testicular tumor, and those who had severe anemia had higher mortality rate. The results of this study indicated that the sensitivity and specificity of the techniques used for BL diagnostis needed to be validated since our studies reveal that children diagnosed using histology had significantly lower mortality rate relative to those who were diagnosed through cytology. This study is helpful in deciding on the feasible therapy and support care system for improving therapeutic strategies and in designing future clinical trials.